Knowledge of Elementary School Students on Menarche Preparation in Karangrejo, Kerjo, Karanganyar, Central Java - Yuniarti, Falasifah Ani; Purwanta, Purwanta; Setyorini, Sasanti (Mutiara Medika: Jurnal Kedokteran dan Kesehatan, 2006)
Teenage is one of child growth periods, characterized by sexual organ maturity, developing capability for reproduction. In girls, this period is usually initiated with menarche. In order for them to be readyfor this period, the girls need sufficient knowledge about menarche.This study was aimed at describing the knowledge level of school-aged children on menarche preparation in Karangrejo, Kerjo, Karang Anyar, Central Java. It was a non- experimental cross-sectional descriptive study. There were 103 respondents who were 5th and 6th grade elementary schools children. Data was collected using a questionnaire and then presented in a frequency distribution table. This study demonstrated that most of the girls had good knowledge of menarche (51.46%), fair knowledge (38.83%), poor knowledge (8.74%) and very poor knowledge (0.97%). Regarding the sources of knowledge they obtained, the results showed that they obtained knowledge from friend (63 children), parents (52 children), printed media (23 children), and teachers (4 children).Usia remaja merupakan salah satu tahap perkembangan anak, dimanateijadi kematangan organ seksual sehingga mampu untuk dapat bereproduksi. Pada anak perempuan hal tersebut biasanya diawali dengan menars. Agar mereka siap dalam menghadapi masa ini, mereka memerlukan pengetahuan yang cukup tentang menars. Penelitian ini bertujuan untuk menggambarkan tingkat pengetahuan anak usia sekolah dalam menghadapi menarche dusun Karangrejo, Keijo, Karang Anyar, Jawa Tengah.Penelitian ini merupakan penelitian deskriptif cross-sectional non- experimental. Terdapat 103 responden yang masih duduk di kelas 5 dan 6 SD. Data dikumpulkan menggunakan kuesioner dan kemudian didistribusikan dalam tabel distribusi frekuensi. Pada penelitian ini didapatkan sebagian besar anak memiliki pengetahuan yang baik (51,46%), pengetahuan yang sedang (38,83%), pengetahuan yang kurang (8,74%) dan pengetahuan yang buruk (0,97%). Mengenai sumber pengetahuan tentang hal tersebut 63 anak memilih teman, 52 anak memilih orang tua. Media cetak dipilih oleh 23 anak, dan guru dipilih 4 anak.